2022
DOI: 10.3389/fpsyg.2022.830031
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Child Abuse Experience and Pathological Internet Use Among Chinese University Students: The Mediating Roles of Security and Maladaptive Cognitions

Abstract: Research has revealed that child abuse experience can increase pathological Internet use; however, few studies have focused on the influence of child abuse experience on pathological Internet use. This study examined the mediating roles of security and maladaptive cognitions in the association between child abuse and pathological Internet use. A total of 918 Chinese university students participated in the study, with measurements of child abuse, security, maladaptive cognitions, and pathological Internet use b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Based on 52,503 students in mainland China from 31 articles, the results of a meta-analysis showed that a moderate Holmanpositive correlation between CT and PIU, consistent with previous research results (Hou et al, 2021a;Qin et al, 2022;Zhang, 2022), it means that students who have experienced CT are more likely to suffer from PIU (Sharifi, 2019;Li, 2020). It supports the Interaction of Person-Affect-Cognition-Execution (I-PACE) model (Brand et al, 2016), according to this model, person's core characteristics, including biological genetic and further bio-psychological factors, are the predisposing factors for the formation of PIU.…”
Section: Relationship Between Childhood Trauma and Problematic Intern...supporting
confidence: 82%
See 1 more Smart Citation
“…Based on 52,503 students in mainland China from 31 articles, the results of a meta-analysis showed that a moderate Holmanpositive correlation between CT and PIU, consistent with previous research results (Hou et al, 2021a;Qin et al, 2022;Zhang, 2022), it means that students who have experienced CT are more likely to suffer from PIU (Sharifi, 2019;Li, 2020). It supports the Interaction of Person-Affect-Cognition-Execution (I-PACE) model (Brand et al, 2016), according to this model, person's core characteristics, including biological genetic and further bio-psychological factors, are the predisposing factors for the formation of PIU.…”
Section: Relationship Between Childhood Trauma and Problematic Intern...supporting
confidence: 82%
“…Grade may also be a moderating variable affecting the relationship between CT and PIU. Some studies found that correlation between CT and PIU of college students was positively correlated to a low degree ( Wei, 2014 ), while other studies found that correlation between CT and PIU of college students was positively correlated to a moderate degree ( Qin et al, 2022 ). In the survey of middle school students, some studies found that there was a low positive correlation between CT and PIU ( Zhang S. J., 2020 ), while others found that there was a moderate positive correlation between CT and PIU ( Du, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, child abuse has brought a lot of adverse effects on individual physical and mental health and subsequent development (Rodriguez et al, 2021). Previous studies have shown that child abuse is related to Internet addiction (Peng et al, 2021a(Peng et al, , 2021bQin et al, 2022;. However, meta-analysis conducting to synthesize their findings was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that child abuse is significantly positively correlated with Internet addiction (Qin et al, 2022;. However, some studies failed to find such association (Hou et al, 2021).…”
Section: The Association Between Child Abuse and Internet Addictionmentioning
confidence: 99%
See 1 more Smart Citation